2019
DOI: 10.1002/ejic.201901030
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity of Woollins' Reagent toward 2‐En‐1‐imines (Schiff Bases): A Facile Approach to Synthesize New Selenium‐Phosphorus‐Nitrogen Heterocycles

Abstract: Woollins' Reagent serves as a reductive cycloaddition reagent, reacting with 2-en-1-imines containing a conjugated C=C bond group (Schiff bases) leading to a series of four-, five-, six-membered 1,2-azaphospholidines incorporating one [a] 4683 in these saturated phosphorus-nitrogen five-membered rings 2c-i (68.8-79.0 ppm). Scheme 4. Cycloaddition derivatives 2j of Schiff base 1j.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 69 publications
0
5
0
Order By: Relevance
“…The reaction between Schiff base derivatives (2-en-1-imines) and [PhP(Se)(μ-Se)] 2 led to the isolation of a series of four-, five-and six-membered 1,2-azaphospholidines containing one or two N-PvSe linkages, as shown in Schemes 10 and 11. 72 Heterocycles 22a and 22b were obtained from the reactions of the corresponding Schiff bases with [PhP(Se)(μ-Se)] 2 via [3 + 2] and [1 + 4] cycloaddition reactions, respectively (Scheme 10). A series of saturated five-membered heterocyclic rings 22c-i were also prepared in moderate to good yields (34-67%) by the reactions of substituted Schiff bases (having a conjugated CvC link) with [PhP(Se)(μ-Se)] 2 involving both cycloaddition and reduction reactions, as shown in Scheme 10.…”
Section: Phosphorus-chalcogen Based Macrocyclesmentioning
confidence: 99%
See 1 more Smart Citation
“…The reaction between Schiff base derivatives (2-en-1-imines) and [PhP(Se)(μ-Se)] 2 led to the isolation of a series of four-, five-and six-membered 1,2-azaphospholidines containing one or two N-PvSe linkages, as shown in Schemes 10 and 11. 72 Heterocycles 22a and 22b were obtained from the reactions of the corresponding Schiff bases with [PhP(Se)(μ-Se)] 2 via [3 + 2] and [1 + 4] cycloaddition reactions, respectively (Scheme 10). A series of saturated five-membered heterocyclic rings 22c-i were also prepared in moderate to good yields (34-67%) by the reactions of substituted Schiff bases (having a conjugated CvC link) with [PhP(Se)(μ-Se)] 2 involving both cycloaddition and reduction reactions, as shown in Scheme 10.…”
Section: Phosphorus-chalcogen Based Macrocyclesmentioning
confidence: 99%
“…However, the source of hydrogen responsible for the reduction process (for 22c-i) is not mentioned in the paper. 72 Surprisingly, under similar reaction conditions, the treatment of a Schiff base having a -SCH 3 group, attached to an aminophenyl ring, with [PhP(Se)(μ-Se)] 2 afforded an unexpected five-membered heterocycle 22j via a [2 + 3] cycloaddition reaction. The reaction pathways for the formation of compounds 22a-j can be described as follows: substitution of one of the bridging selenium atoms in [PhP(Se)(μ-Se)] 2 by the CvN group of the Schiff base resulted in five-membered heterocycle 22a, whereas the formation of 22b was due to the cycloaddition of a PvSe bond across the CvC-CvN bond involving a six-membered intermediate which eventually lost a Se atom.…”
Section: Phosphorus-chalcogen Based Macrocyclesmentioning
confidence: 99%
“…The chemistry of 2,4-bis­(phenyl)-1,3-diselenadiphosphetane-2,4-diselenide (Woollins’ reagent, WR) has been developed and exploited widely by us and other groups as a versatile selenation reagent or synthetic precursor in synthetic chemistry. Recently, we have reported that Woollins’ reagent can add to the CN bond of a series of conjugated Schiff bases to generate a series of stable five-membered phosphorus–selenium–nitrogen heterocycles . In continuation of our interest in the chemistry of WR toward various organic substrates, we report herein the reactivity of WR toward amido-Schiff bases, which led to the formation of a series of five- and six-membered P–Se heterocycles and their related X-ray structures.…”
Section: Introductionmentioning
confidence: 99%
“…18−31 Recently, we have reported that Woollins' reagent can add to the CN bond of a series of conjugated Schiff bases to generate a series of stable five-membered phosphorus−selenium−nitrogen heterocycles. 32 In continuation of our interest in the chemistry of WR toward various organic substrates, we report herein the reactivity of WR toward amido-Schiff bases, which led to the formation of a series of fiveand six-membered P−Se heterocycles and their related X-ray structures. To the best of our knowledge, this is the first reported synthesis and single-crystal structures of such small ring phosphorus−selenium heterocycles incorporating single Se−PSe or N−PSe linkage.…”
Section: ■ Introductionmentioning
confidence: 99%
“…This reagent has been explored for its selenating property in various substrates encompassing carbonyl compounds, double and triple C–C bonds, C–N triple bonds, and Schiff bases, among others, resulting in a wide range of products such as selenium heterocycles, selenoamides, selenoic Se-acids, and four–ten-membered selenophosphorus heterocycles. 3–5 Furthermore, its reductive potential has been explored in carbonyl and α,β-unsaturated compounds. 6 A few examples pertaining to the reactivity of WR are delineated in Fig.…”
mentioning
confidence: 99%